Cultivating Femininity Women and Tea Culture in Edo and Meiji Japan - Corbett, Rebecca (University of Hawai'i Press, 2018)
The overwhelming majority of tea practitioners in contemporary Japan are women, but there has been little discussion on their historical role in tea culture (chanoyu). In Cultivating Femininity, Rebecca Corbett writes women back into this history and shows how tea practice for women was understood, articulated, and promoted in the Edo (1603-1868) and Meiji (1868-1912) periods. Viewing chanoyu from the lens of feminist and gender theory, she sheds new light on tea's undeniable influence on the formation of modern understandings of femininity in Japan. Cultivating Femininity offers a new perspective on the prevalence of tea practice among women in modern Japan. It presents a fresh, much-needed approach, one that will be appreciated by students and scholars of Japanese history, gender, and culture, as well as by tea practitioners.